Lipid and glucose metabolism of broilers (Gallus gallus domesticus) experimentally infected with Eimeria acervulina Tyzzer, 1929 oocysts - Freitas, FLC [UNESP]; Almeida, KS; Machado, RZ [UNESP]; Machado, CR [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2008)
Lipid and glucose metabolism of 76 ten-day-old Cobb male broilers, experimentally infected with Eimeria acervulina, was studied for 30 days. Birds were distributed in 2 groups: one infected with 1x10(6) E. acervulina sporulated oocysts, and the other inoculated with distilled water. Pathological e biochemical liver changes were assessed, as well as plasma glucose concentrations and total cholesterol, HDL, LDL, VLDL, fatty-acid, and triglyceride levels in the serum. The infected broilers presented hypoglycemia associated with a reduction in liver glycogen. In addition, these birds developed fatty liver, and there were changes in all lipid classes in the serum. Lipid and glucose metabolism was dramatically changed in broilers experimentally infected with 1x10(6) E. acervulina oocysts.
Keywords: Broilers; Eimeria acervulina; Fatty acids; Glucose; total cholesterol; Triglycerides